P3.073 Performance of Self-Collected Vaginal Swabs in Diagnosis of Bacterial Vaginosis Among Young Reproductive Age Women in Mysore, India. (13th July 2013) - Srinivas, V; Ravi, K; Arun, A; Niranjankumar, B; Shaheen, R; Jaykrishna, P; Krupp, K; Madhivanan, P
Abstract : Background: Culturally, women are less inclined to undergo a per-speculum examination for screening of reproductive tract infections and consider self-sampling more acceptable. This study examines the concordance between Gram stains of vaginal smears and pH obtained by clinician conducted speculum examination with similar smears and pH prepared from self-collected vaginal swabs. Methods: Between June 2010 and 2012, self-collected (SVS) and clinician-collected vaginal (CVS) swabs were obtained from 79 young reproductive age women attending the Prerana Reproductive Health Clinic in Mysore, India. The study was explained to each participant and a brochure illustrating how to collect vaginal swabs was handed to them. The Gram-stained smears and saline wet mounts prepared from the SVS and CVS were examined by a trained microbiologist and the clinician. Vaginal pH was recorded for each swab. Kappa coefficient was used to quantify agreement between the two sets of results. Results: When compared with the CVS, the ability of the self-obtained Gram stain to diagnose bacterial vaginosis had a sensitivity of 100%, specificity of 98%, positive predictive value of 100% and negative predictive value of 100%. Only one pair was discordant in the results where the SVS showed the BV status as negative while the CVS found it to be intermediate stage BV. There was substantial agreement (kappa = 0.97) between the two collection methods in the ability to determine the grade of vaginal flora. Conclusion: As compared with clinician collected vaginal smears, self-collected smears have substantial agreement in the diagnosis of bacterial vaginosis. With adequate education and instructions using simple visual illustrations, it is possible to have women sample and self collect vaginal swabs for diagnosis of lower genital tract infections.